al-ʻUmānīyūn fī Sharq Ifrīqiyā: Tārīkh wa-Ḥaḍārah — Zanjibār Namūdhajan - Lūṣīf, Sufyān (al-Muʼtamar al-Duwalī: al-Dawr al-ʻUmānī fī Waḥdat al-Ummah, 2014)
Oman has been known since ancient times for its leadership and its maritime and navigational role, and for its great and historic ties with the ancient civilizations, particularly the Sumerian, Babylonian, Roman and Pharaonic, among other civilizations and peoples in different periods. Omanis were in the vanguard of the pioneers of the oceans, whose ventures and voyages were counted a model of enterprise, daring and courage. This role was without doubt reflected in economic life in Oman, and Oman took on a great part in activating maritime trade between Asia and Africa by virtue of its position and its connection with the African coast and the entrance to the seas of India and China — so that it is no wonder some historians called the Omanis the pioneers of navigation from the earliest times. This study examines the Omani presence in East Africa with Zanzibar as its case study.
MHF-OMANIUNITY-015
Keywords: Zanzibar; East Africa; Omani navigation; Maritime history; Civilization; Indian Ocean